As you sow, so shall you reap - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Availability of good quality seeds for sowing makes or breaks food production worldwide. It is an age-old issue, for which in the course of time countless smart and cunning technical solutions have been developed. The Green Revolution is one such....